Intellectual Property Rights Law Reform Based on Maqāṣid al-Sharī‘ah as a Model for Green Business-Based Creative Industry Protection to Support Sustainable Development - Nina Nurani; Apriwandi Apriwandi; Hafied Noor Bagja (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2026)
This research is motivated by the normative tension between the intellectual property rights (IPR) legal regime, which is oriented towards exclusive rights and economic certainty, and the demands of social welfare and sustainable development. Although IPR functions as an instrument to incentivize innovation, its normative structure tends to result in unequal access and the dominance of capitalist actors, and it has not explicitly integrated the principle of sustainability. This article aims to reconstruct a model for IPR legal reform based on maqāṣid al-sharī‘ah as a normative framework capable of balancing rights protection, distributive justice, and ecological sustainability. The research method employed is normative legal research with a statutory, conceptual, and comparative approach, which is analysed through the construction of maqāṣid al-sharī‘ah. The results show that the Indonesian IPR regime still adheres to an exclusivist-proprietarian paradigm that protects individual ownership and economic benefits but has not yet internalised the principles of maṣlaḥah, ‘adl, and sustainability. The integration of maqāṣid produces a normative model that repositions exclusive rights as conditional rights subject to the public interest, the distribution of benefits, and environmental protection. The conclusion confirms that IPR remains valid as a protection of property and intellect, but must be limited by the principles of social justice and sustainability. The limitation of this study lies in the normative approach that has not examined empirical implementation. The implication of this research is the need to reorient IPR law towards a more inclusive and sustainable system. The novelty of this article lies in the use of maqāṣid al-sharī‘ah as a framework for the normative reconstruction of IPR that comprehensively integrates economic, social, and ecological dimensions. Keywords: intellectual property; law; maqāṣid al-sharī‘ah; creative industry; sustainable development.